EVALUASI PENGGUNAAN MODUL INTERAKTIF BATUK DAN SESAK SEBAGAI MEDIA PEMBELAJARAN MANDIRI STASE KOMPREHENSIF - Winarto Winarto; Firdaus Firdaus; Rossa Kamila Maharani (LPPM Institut Pendidikan Nusantara Global, 2023)
The Cough Shortness interactive module is a medium that was developed to facilitate students' independent learning at the comprehensive stage, in order to increase the graduation rate for UKMPPD participants at the Faculty of Medicine, University of Riau. This study aims to determine the success of an interactive module that was developed by measuring the increase in user knowledge of the module and the level of user acceptance (usability). This research is a quantitative study using an experimental one group pretest post-test design to assess increased knowledge and quantitative descriptive to see user acceptance of the cough and tightness interactive module using 2 questionnaires, namely the System Usability Scale (SUS), User Experience Questionnaire (UEQ) . This research was conducted at the Faculty of Medicine, University of Riau in September – November 2022. The results of this study showed an increase in mana knowledge with a different test between the average pre-test score of 57.91 and the average post-test of 82.83, paired sample T-test shows the difference with sig. (2–tailed) of 0.000 (p <0.05). The SUS score of 71 indicates that the interactive cough shortness module is developed in the acceptability ranges obtained are